Innovation Management as a Tool for Sustainable Development and Improving the Quality of Life of Societies - Aleksandra KUZIOR (Communications of International Proceedings, 2021)
The article is theoretical and addresses the issues of implementing the assumptions and goals of sustainable development based on product innovations, process innovations and disruptive innovation. In the concept of sustainable development, innovations are recognized as an instrumental value and a tool for shaping better living conditions, work, rest and all forms of human activity, as well as environmental protection. The article presents the issues of innovation management and innovation marketing based on the analysis of the literature on the subject and selected examples of practical applications. The article refers to examples of ecological innovations and innovations for safety and improvement of the quality of life, indicating that one of the best tools for creating innovations is foresight, understood as the process of researching the future. The author also draws attention to the necessity of ethical education of engineers and shaping attitudes of responsibility for the products of engineering creativity (innovation).
Keywords: Management Innovation; Sustainable Development; Quality of Life; Marketing of Innovation